Dimeric subunit stoichiometry of the human voltage-dependent proton channel Hv1 - Lee, Seok-Yong (National Academy of Sciences, 2008)
In voltage-gated Na(+), K(+), and Ca(2+) channels, four voltage-sensor domains operate on a central pore domain in response to membrane voltage. In contrast, the voltage-gated proton channel (Hv) contains only a voltage-sensor domain, lacking a separate pore domain. The subunit stoichiometry and organization of Hv has been unknown. Here, we show that human Hv1 forms a dimer in the membrane and define regions that are close to the dimer interface by using cysteine cross-linking. Two dimeric interfaces appear to exist in Hv1, one mediated by S1 and the adjacent extracellular loop, and the other mediated by a putative intracellular coiled-coil domain. It may be significant that Hv1 uses for its dimer interface a surface that corresponds to the interface between the voltage sensor and pore in Kv channels.